ETIKA PENGGUNAAN KOMPUTER DI TEMPAT KERJA (STUDI KASUS DI INDONESIA) - Dety Nurfadilah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2016)
This research seeks to understand the employee's perception as well as to investigate personal characteristics which can influence the employee's attitude towards computer use ethics at the workplace. The personal characteristics that are being discussed here are gender, job satisfaction, religious belief and position in the organization. The research design involved the collection of in-depth and semi-structured interviews from six people in the private sector and four people in the public sector. From the total of 10 respondents, there were five males and five females. The result found that computer use ethics is important in the organization modern and must be addressed by employers tactfully. Respondents also agreed that position in organization and religious belief have the biggest impact in guiding and influence employees towards ethical computer usage at work.